PERSEPSI MASYARAKAT TERDAMPAK BENCANA TERHADAP OPERASI PENCARIAN DAN PERTOLONGAN GEMPA BUMI KELURAHAN CIPAMEUNGPEUK RT.01/RW.03 KECAMATAN SUMEDANG SELATAN - Sahrul Hidayat; Ilham Badaruddin Mataburu; Ode Sofyan Hardi (Jurnal Geografi, 2026)
This study aims to determine the perceptions of earthquake-affected communities regarding search and rescue operations during the Sumedang earthquake emergency, West Java. Cipameungpeuk Village has a moderate earthquake risk index. The earthquake occurred between December 2023 and January 2024. The results of the search and rescue operation procedures reported limited time and equipment during the operation, resulting in an increase in the number of affected people. Using the ex-post facto method to determine the perceptions of those affected based on gestalt theory, ecological perception theory related to region, situation, and environment, as well as the main SAR operation indicators from BASARNAS. Using perception analysis, the affected community was classified as the main factor in reviewing the response time of search and rescue operations. The results showed that approximately 60% of the community perceived search and rescue as adequate, but 40% of respondents with a positive perception suggested evaluation and operational time training. This study provides a social perspective in disaster geography.